2019
DOI: 10.1002/ptr.6261
|View full text |Cite
|
Sign up to set email alerts
|

Identification of higenamine as a novel α1‐adrenergic receptor antagonist

Abstract: The α1‐adrenoceptor (α1‐AR) antagonists are potential candidates for the treatment of blood pressure. Higenamine (HG) is a novel α1‐AR antagonist. In this study, we investigated the effects of HG in HEK293A cells transfected with α1A‐, α1B‐, and α1D‐AR in vitro, rat mesenteric artery ex vivo, Wistar–Kyoto rats and spontaneously hypertensive rats in vivo. The radioligand binding assay showed that HG competitively inhibited the binding of [3H]‐prazosin to α1‐AR in a concentration‐dependent manner. The affinities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…β2‐AR activation explains the pharmacological effect of HG/aconite in treating CHF by enhancing the contractile response and reducing cardiomyocyte apoptosis . Also, HG is identified as a novel α1‐AR antagonist, which may contribute to its hypotensive effect and suppression platelet aggregation . Pharmaceutically, it has multiple pharmacological effects, including positive inotropic effect, dilations of blood vessels and bronchi, anti‐inflammatory activity, antispasmodics, anti‐thrombotic, anti‐oxidative and anti‐apoptotic properties .…”
Section: Introductionmentioning
confidence: 99%
“…β2‐AR activation explains the pharmacological effect of HG/aconite in treating CHF by enhancing the contractile response and reducing cardiomyocyte apoptosis . Also, HG is identified as a novel α1‐AR antagonist, which may contribute to its hypotensive effect and suppression platelet aggregation . Pharmaceutically, it has multiple pharmacological effects, including positive inotropic effect, dilations of blood vessels and bronchi, anti‐inflammatory activity, antispasmodics, anti‐thrombotic, anti‐oxidative and anti‐apoptotic properties .…”
Section: Introductionmentioning
confidence: 99%
“…Isoflavones, a flavonoid from red clover (Trifolium pratense), exhibited a relaxant effect on the smooth muscles of isolated guinea-pigs' ilea [44], rats' uteri [45], guinea-pigs' gall bladders [46] and rats' prostate glands [31]. Furthermore, a variety of flavonoids derived from various plant materials possessed α1-adrenergic receptor antagonists and reduced the contraction of the prostate smooth muscles of experimental animals [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…β-sitosterol has been detected in ethyl acetate extracts from U. rufa stems [28]. Different types of flavonoids, alkaloids and sterols derived from various plant materials possessed α1-adrenergic receptor antagonists and exhibited relaxation effects on the dynamic component in the prostate gland of experimental animals [29][30][31][32]. Although there is a lot of research being done on the phytochemical composition of C. sappan and U. rufa, there is no detailed information about their relaxant properties on the prostate smooth muscles.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Zhang et al (2019) suggested that higenamine, directly binding to α1-adrenergic receptors, could be an innovative α1-adrenergic receptor antagonist. In particular, in different models of hypertension (normotension and spontaneous hypertension), higenamine was able to decrease the blood pressure (Zhang et al 2019).…”
Section: Higenaminementioning
confidence: 99%